Genetic variation in cell cycle regulatory gene AURKA and association with intrinsic breast cancer subtype. Issue 12 (18th October 2014) - Taylor, Nicholas J.; Bensen, Jeannette T.; Poole, Charles; Troester, Melissa A.; Gammon, Marilie D.; Luo, Jingchun; Millikan, Robert C.; Olshan, Andrew F.
<x xml:space="preserve">Abstract</x> AURKA is a putative low‐penetrance tumor susceptibility gene due to its prominent role in cell cycle regulation and centrosomal function. Germline variation in AURKA was evaluated for association with breast cancer and intrinsic breast cancer subtypes in the Carolina Breast Cancer Study (CBCS), a population‐based case‐control study of African Americans (AA) and Caucasians (Cau). Tag and candidate single nucleotide polymorphisms (SNPs) on AURKA were genotyped in 1946 cases and 1747 controls. In race‐stratified analyses adjusted for age and African ancestry, odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to evaluate SNP associations with breast cancer. In a race‐combined analysis with similar adjustment, these associations were also examined by intrinsic breast cancer subtype. Using dominant models, most AURKA SNPs demonstrated no association with breast cancer in the race‐stratified analyses. Among AA, rs6092309 showed an inverse association with breast cancer (OR = 0.69, 95% CI = 0.53–0.90). In the race‐combined analyses, rs6099128 had reduced ORs for luminal A (OR = 0.76, 95% CI = 0.60–0.95) and basal‐like breast cancer (OR = 0.54, 95% CI = 0.37–0.80). Rs6092309 showed a similar pattern of association with each subtype. Three SNPs (rs6014711, rs911162, rs1047972) had positive associations with basal‐like breast cancer, and ORs reduced or close to 1.00 for other subtypes. Our results suggest inverse associations between some AURKA SNPs and overall breast cancer in AA. We found differential associations by specific subtypes and by race. Replication of these findings in larger AA populations would allow more powerful race‐stratified subtype analyses. © 2014 Wiley Periodicals, Inc.